Disinformation among students arriving at university to pursue degrees related with information science. The cases of Brazil, Cuba and Spain - Presser, Nadi Helena; Pacios , Ana R.; Bernades da Silva, Abinair (Revista General de Información y Documentación, 2024)
The article presents the findings of a study conducted as part of a research project about misinformation and disinformation. The study was performed with the cooperation of 16 universities from three Ibero-American countries (Brazil, Cuba and Spain) and the participation of 428 students just beginning their studies for a degree related with information science. The objective was to learn if students newly arrived at university and enrolled in information science degree programmes have the competences needed to detect disinformation and know how to react or behave when news reaches them. Information was collected using a 26-item questionnaire with open and closed answers about the target issues. The results show that a high percentage of students have trouble recognizing news that they receive over social networks as fake and do not use content or context criteria or indicators to determine whether to believe the information they receive or find on social networks. Over 36% rely on their own prior knowledge and opinions. A little more than half of the students (61.9%) claim to verify information at the original source to evaluate its reliability. Surprisingly passive behaviour was found among those students (34.8%) who are unaware of how much incorrect information they receive, and a striking number of students (31.5%) reported having shared some kind of disinformation.